On the Kinetic and Allosteric Regulatory Properties of the ADP-Glucose Pyrophosphorylase from Rhodococcus jostii: An Approach to Evaluate Glycogen Metabolism in Oleaginous Bacteria - Cereijo, Antonela E.; Asencion Diez, Matías D.; Dávila Costa, José S.; Alvarez, Héctor M.; Iglesias, Alberto A. (Frontiers in Microbiology, 2016)
Rhodococcus spp. are oleaginous bacteria that accumulate glycogen during exponential growth. Despite the importance of these microorganisms in biotechnology, little is known about the regulation of carbon and energy storage, mainly the relationship between glycogen and triacilglycerols metabolisms. Herein we report the molecular cloning and heterologous expression of the gene coding for ADP-glucose pyrophosphorylase (EC 2.7.7.27) of Rhodococcus jostii, strain RHA1. The recombinant enzyme was purified to electrophoretic homogeneity to accurately characterize its oligomeric, kinetic and regulatory properties. The R. jostii ADP-glucose pyrophosphorylase is a homotetramer of 190 kDa exhibiting low basal activity to catalyze synthesis of ADP-glucose, which is markedly influenced by different allosteric effectors. Glucose-6P, mannose-6P, fructose-6P, ribose-5P and phosphoenolpyruvate were major activators; whereas NADPH and 6P-gluconate behaved as main inhibitors of the enzyme. The combination of glucose-6P and other effectors (activators or inhibitors) showed a cross-talk effect suggesting that the different metabolites could orchestrate a fine regulation of ADP-glucose pyrophosphorylase in R. jostii. The enzyme exhibited some degree of affinity toward ATP, GTP, CTP, and other sugar 1P substrates. Remarkably, the use of glucosamine-1P was sensitive to allosteric activation. The relevance of the fine regulation of R. jostii ADP-glucose pyrophosphorylase is further analyzed in the framework of proteomic studies already determined for the bacterium. Results support a critical role for glycogen as a temporal reserve that provides a pool of carbon able of be re-routed to produce long-term storage of lipids under certain conditions.